2021
DOI: 10.3390/app112210684
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar Rotary Friction Welding of Inconel 718 to F22 Using Inconel 625 Interlayer

Abstract: Dissimilar metal joining has always been a challenging task because of the metallurgical incompatibility and difference in melting points of alloys being joined. Diffusion and mixing of alloying elements from dissimilar base metals at the weld often cause unwanted metallurgical changes resulting in unsuccessful welds or underperformance of the weldment. Solid-state dissimilar friction welds of Inconel 718 and F22 were prepared in this study with an Inconel 625 interlayer to address the carbon enrichment of Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Nowadays in many branches of industry that can be regarded as critic for national or global economy there is a strong need for new technologies and materials. Production of electric energy [ 1 , 2 ], off-shore and marine industry and engineering [ 3 , 4 ] nuclear industry [ 5 ] also in applications connected with green production and environment protection a vast of areas where are harsh conditions including corrosive environments, where the most dangerous is gas corrosion in elevated temperatures of operation [ [6] , [7] , [8] , [9] , [10] ]. Possibility to operate in conditions where there is a high amount of heat in the surrounding environment [ 11 , 12 ], significant resistance for creeping (mainly in high temperatures over 1000 °C) [ [13] , [14] ] are only some of requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays in many branches of industry that can be regarded as critic for national or global economy there is a strong need for new technologies and materials. Production of electric energy [ 1 , 2 ], off-shore and marine industry and engineering [ 3 , 4 ] nuclear industry [ 5 ] also in applications connected with green production and environment protection a vast of areas where are harsh conditions including corrosive environments, where the most dangerous is gas corrosion in elevated temperatures of operation [ [6] , [7] , [8] , [9] , [10] ]. Possibility to operate in conditions where there is a high amount of heat in the surrounding environment [ 11 , 12 ], significant resistance for creeping (mainly in high temperatures over 1000 °C) [ [13] , [14] ] are only some of requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel alloys in both categories can be welded using common processes [ 33 ]. Rehman et al [ 34 ] investigated the mechanical properties and microstructure of Inconel 718-F22 RFW joints. The results revealed that the higher hardness was observed at the weld interface of the Inconel 718/2.5Cr-1Mo (F22) steel RFWed joints compared with the RFWed joints with an Inconel 625 interlayer.…”
Section: Introductionmentioning
confidence: 99%
“…This may be attributed to the strain hardening of the FDZ of Inconel 718 in AISI 316L/IN 718 ST, which is higher compared to the AISI 316L/IN 718 STA condition. IN 718 ST softened at a temperature lower than IN 718 STA, resulting in severe plastic deformation[36].Due to the peak temperatures and high strain energy encountered by the FDZ of IN…”
mentioning
confidence: 99%